Dados epidemiológicos sobre a infecção por Sarcocystis spp., Neospora spp. e Toxoplasma gondii em equídeos do Pantanal brasileiro - Borges, Alice Mamede Costa Marques (2018)
Sarcocystis neurona a causative agent of equine protozoal myeloencephalitis (EPM) is a serious neurologic disease of horses. The opossum are definitive hosts for S. neurona (Didelphys virginiana, the North American and D. albiventris, in South American). Neosporosis is caused for N. caninum and N. hughesi in horses also cause abortion, reprodutive problems. The definitive hosts for N. caninum are dogs and coyotes and the definitive hosts for N. hughesi is unknown. Toxoplasma gondii, parasite of worldwide distribuition and cause of toxoplasmosis, zoonosis of medical and veterinary importance. Domestic and wild felids are the definitive hosts and humans and virtually all warm-blooded species may be intermediate hosts. The horse breeding is an essential segment of agribusiness in Mato Grosso State and the important in the Pantanal because they are indispensable for live-stock management and provide a practical means of transport. Protozoa from the family Sarcocystidae are acquired through the ingestion of contaminated food and water, which can cause neurological and reproductive disorders in horses, causing damage to breeders. Although some epidemiological data for these protozoa are known, such as transmission routes and hosts, particular information to distinct regions such as the Pantanal of Mato Grosso are unknown. The objectives of the present study were to evaluate the presence of antibodies against Sarcocystis neurona, Neospora spp. and Toxoplasma gondii, their main forms of maintenance in equidae of the region, giving subsidies for a better understanding of these diseases in this species.